Learning and Teaching in Public Spaces (LTPS) : Final Report. - Ryan, Maureen; Charman, Karen (Office for Learning and Teaching, 2014)
Museums are underutilised learning spaces by universities in Australia. Practice-based learning exchanges with museums, such as the Humanities and Education programs at Victoria University (VU) and Deakin University, have the potential to foster the acquisition of cross-disciplinary skills, including personal attributes such as citizenship through civic engagement. This project created a national resource which promotes and enables Higher Education (HE) collaboration with partner museums, by providing pedagogical support for curriculum renewal in pre-service education, social science and humanities course programs. The project distilled the principles into a framework for effective collaboration with museums, and produced guides and a digital resource that, with ongoing support, will enable the embedding of the new curricula into two new institutional sites (Queensland University of Technology, Charles Sturt University). This is the final report from the project.